2011
DOI: 10.1111/j.1365-2435.2011.01910.x
|View full text |Cite
|
Sign up to set email alerts
|

Gregarious flowering and death of understorey bamboo slow litter decomposition and nitrogen turnover in a southern temperate forest in Patagonia, Argentina

Abstract: Summary1. The massive synchronized flowering and subsequent mortality of understorey bamboo species occur in infrequent and unpredictable intervals in temperate and subtropical forests around the world. Because of the sporadic occurrence of these flowering episodes and the long intervals between events, very little is known about their consequences on biogeochemical cycling in natural ecosystems. 2. In 2001, a synchronized flowering and dieback of the native bamboo, Chusquea culeou E. Desv., occurred, covering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 68 publications
(152 reference statements)
2
24
1
1
Order By: Relevance
“…Decomposition of bamboo litter was slower on average than rates of mass loss in other subtropical forests (Deka and Mishra, 1982;Singh and Singh, 1999), and substantially reduced compared to the subdominant tree species such as S. bonplandii. Our results were similar to the findings of Liu et al (2000) in a subtropical mountain forest in China for the bamboo Sinarundinaria nitida, which requires more than 6 years to lose 95% of their initial mass, and consistent with another study of Chusquea bamboo flowering which demonstrated significantly slower decomposition of bamboo litter, particularly stem tissue (Austin and Marchesini, 2011). The slow decomposition rates of C. ramosissima leaves could be the result of several factors.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Decomposition of bamboo litter was slower on average than rates of mass loss in other subtropical forests (Deka and Mishra, 1982;Singh and Singh, 1999), and substantially reduced compared to the subdominant tree species such as S. bonplandii. Our results were similar to the findings of Liu et al (2000) in a subtropical mountain forest in China for the bamboo Sinarundinaria nitida, which requires more than 6 years to lose 95% of their initial mass, and consistent with another study of Chusquea bamboo flowering which demonstrated significantly slower decomposition of bamboo litter, particularly stem tissue (Austin and Marchesini, 2011). The slow decomposition rates of C. ramosissima leaves could be the result of several factors.…”
Section: Discussionsupporting
confidence: 93%
“…The short-term effects on tree sapling growth were due to significant increment in light availability during the first year after bamboo flowering which was quickly reverted due to rapid colonization by other herbaceous understory species. At the same time, many other environmental characteristics such as litter decomposition and soil nutrient concentrations were largely unaffected by the flowering event, which is contrasts with results from temperate Argentine forests (Giordano et al, 2009;Austin and Marchesini, 2011). Successful tree growth in gaps following bamboo flowering appears to be restricted to a very narrow window of increased resource availability, and only some already established individuals were able to take advantage of the increasing resources.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…Variations in flowering time are not only diverse among species, but also at the population level. For instance, in the case of gregarious flowering all the individuals of a species growing over a wide geographical area bloom within a brief interval of time, and then all die after flowering (Nadgauda et al, 1997; Bhattacharya et al, 2009; Marchesini et al, 2009; Austin and Marchesini, 2012; Chaubey et al, 2013; Xie et al, 2016). In contrast, for sporadic flowering only a few culms of a population flower at a time (Ramanayake and Yakandawala, 1998; Bhattacharya et al, 2006; Xie et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…). Austin & Marchesini () showed that leaf and stem litters of understorey bamboo ( Chusquea culeou E. Desv.)…”
Section: Introductionmentioning
confidence: 99%